Using the principle of mathematical induction, prove each of the following for all n ϵ N:

2 + 4 + 6 + 8 + …. + 2n = n(n + 1)


To Prove:


2 + 4 + 6 + 8 + …. + 2n = n(n + 1)


Steps to prove by mathematical induction:


Let P(n) be a statement involving the natural number n such that


(i) P(1) is true


(ii) P(k + 1) is true, whenever P(k) is true


Then P(n) is true for all n ϵ N


Therefore,


Let P(n): 2 + 4 + 6 + 8 + …. + 2n = n(n + 1)


Step 1:


P(1) = 1(1 + 1) = 1 × 2 = 2


Therefore, P(1) is true


Step 2:


Let P(k) is true Then,


P(k): 2 + 4 + 6 + 8 + …. + 2k = k(k + 1)


Now,


2 + 4 + 6 + 8 + …. + 2k + 2(k + 1) = k(k + 1) + 2(k + 1)


= k(k + 1) + 2(k + 1)


= (k + 1) (k + 2)


= P(k + 1)


Hence, P(k + 1) is true whenever P(k) is true


Hence, by the principle of mathematical induction, we have


2 + 4 + 6 + 8 + … + 2n = n(n + 1) for all n ϵ N


1